Optimalisasi Peran BUMDESMA dalam Sosialisasi Sertifikat Halal pada Produk Home Industri di Desa Kaliboto Kecamatan Tarokan Kabupaten Kediri - Hafil, Ach. Shodiqil; Hajar, Lutfiatul Nurul; Anisa, Anisa; Manfi’ah, Siti Wachidatul; Hanafi, Alif; Khoiruttajubba, Kurnia Haqmalia; Asy’ari, Asy’ari (Dharma Sevanam : Jurnal Pengabdian Masyarakat, 2024)
The food and beverage sector from home industries significantly impacts the community's welfare. P-IRT permits and halal certification are crucial for ensuring product safety and gaining consumer trust. According to Consumer Protection Law No. 8 of 1999, consumers have the right to safe products. In Kaliboto Village, the number of MSMEs is increasing, but many still lack halal certification, despite its mandatory status following the implementation of Industry Law No. 03 of 2014. This study aims to provide socialization and assistance to home industry players in obtaining halal certification. The method used includes identifying needs, preparing socialization materials, conducting socialization, post-socialization assistance, and evaluation. The results show that many home industry players in Tarokan District lack business legality and halal certification, due to a lack of knowledge and awareness of its importance. The socialization conducted by BUMDESMA Kaliboto Village helps increase understanding among business actors about the process and benefits of halal certification and encourages BUMDESMA to be more active in supporting this process. With socialization and assistance, it is expected that home industry players can more easily obtain halal certification, ultimately increasing income and improving the welfare of the village community.